2020
DOI: 10.3390/ani10030527
|View full text |Cite
|
Sign up to set email alerts
|

Development of Swine’s Digestive Tract Microbiota and Its Relation to Production Indices—A Review

Abstract: The development of research methods and tools related to microbiome investigation, as well as widened knowledge and awareness concerning the significance of microorganisms inhabiting mammalian organisms, has led to an increasing popularity of studies in this field. This review paper presents some issues related to the swine microbiome, its development starting from an early age of life and its status in adult animals, as well as factors affecting the microbiome in pigs. Attention is paid to the role of probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 99 publications
1
49
0
3
Order By: Relevance
“…Yang et al [ 60 ] previously reported that the gut microbial shifts affected meat quality and took a crucial role as the major contributor to adiposity in pigs. Several studies reported the relationships between microbial compositions and carcass characteristics and showed higher abundance of Lactobacillus , Oscilibacter , Roseburia , and Clostridium in pigs with high-quality pork compared to those in pigs with low-quality pork [ 61 , 62 ]. Park et al [ 61 ] showed that the relative abundance of those four genera was 5% higher in pigs with high-quality pork compared to those in pigs with low-quality pork.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 60 ] previously reported that the gut microbial shifts affected meat quality and took a crucial role as the major contributor to adiposity in pigs. Several studies reported the relationships between microbial compositions and carcass characteristics and showed higher abundance of Lactobacillus , Oscilibacter , Roseburia , and Clostridium in pigs with high-quality pork compared to those in pigs with low-quality pork [ 61 , 62 ]. Park et al [ 61 ] showed that the relative abundance of those four genera was 5% higher in pigs with high-quality pork compared to those in pigs with low-quality pork.…”
Section: Discussionmentioning
confidence: 99%
“…A single study suggested that the rate of average daily gain of piglets could be associated with a characteristic oropharyngeal microbial signature and that manipulating the oropharyngeal microbiota in pre-weaned piglets could influence weight gain [56]. In addition, several reports have shown the importance of the gut microbiome in pig productivity through its effects on digestion, feed efficiency and immune stimulation [57]. These studies suggest that there might be close relationship between the microbial community colonizing different body sites, including the respiratory tract, and animal's weight gain and other productivity parameters.…”
Section: Relationship Of the Respiratory Microbiome With Diseasementioning
confidence: 99%
“…In humans, this window of time has been established as 100 days [ 56 ], a period during which dysbiosis and shifts in specific bacterial taxa have been related to an increased risk of asthma in future life [ 57 ]. While something similar is expected to occur in pigs [ 57 , 58 ], further research is needed to understand the impact of early life events on the piglet’s microbiome and its potential relevance for the pig industry [ 59 , 60 , 61 ]. Some authors have described how different exposure levels to stress or the use of antibiotics can determine changes in the gut microbial colonization of pigs eight days after birth with implications for immunity development [ 62 ].…”
Section: Factors Affecting the Weaning Bwmentioning
confidence: 99%